2016
DOI: 10.1002/cphc.201501124
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Design Guidelines for Large Magnetic Circular Dichroism Intensities in Lanthanide Complexes

Abstract: Magneto optical devices based on the Faraday effects of lanthanide ion have attracted much attention. Recently, large Faraday effects were found in nano-sized multinuclear lanthanide complexes. In this study, the Faraday rotation intensities were estimated for lanthanide nitrates [Ln(III) (NO3 )3 ⋅n H2 O: Ln=Pr, Nd, Sm, Eu, Tb, Dy, Ho, Er, Tm) and Eu(III) complexes with β-diketone ligands, using magnetic circular dichroism. Eu ions exhibit the largest Faraday rotation intensity for (7) F0 →(5) D1 transitions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 34 publications
(18 reference statements)
0
24
0
Order By: Relevance
“…Another feature is that the magnetic field parallel to and antiparallel to the light propagation direction have completely opposite effects on the CD signal: the positive direction magnetic field (+1.6 T) has a negative effect on the CD signal; on the contrary, the negative direction magnetic 45 and 4f complexes (≤0.24 T −1 ). 93 The large absolute value of g max(MCD) for the chiral Dy 2 enantiomers D-1 and L-1 indicates a very strong magneto-optical Faraday effect. Recent studies have shown that, for lanthanide (III) compounds, the strength of MCD can be enhanced by increasing the magnetic dipole moment of the ground states and the excited states.…”
Section: ■ Results and Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Another feature is that the magnetic field parallel to and antiparallel to the light propagation direction have completely opposite effects on the CD signal: the positive direction magnetic field (+1.6 T) has a negative effect on the CD signal; on the contrary, the negative direction magnetic 45 and 4f complexes (≤0.24 T −1 ). 93 The large absolute value of g max(MCD) for the chiral Dy 2 enantiomers D-1 and L-1 indicates a very strong magneto-optical Faraday effect. Recent studies have shown that, for lanthanide (III) compounds, the strength of MCD can be enhanced by increasing the magnetic dipole moment of the ground states and the excited states.…”
Section: ■ Results and Discussionmentioning
confidence: 66%
“…The anisotropy factor of MCD, g MCD = 2­(ε + ( B ) – ε + (− B ))/(ε + ( B ) + ε + (− B )), was calculated for both l - 1 and d - 1 (Figure ), which have a roughly mirror symmetry in the 250–350 nm range. Notably, the values of g max(MCD) for l - 1 and d - 1 at room temperature are 1.27 and −1.72 T –1 , respectively, whose absolute values are remarkably large values, much larger than those of 3d–4f complexes [Co 2 Ln­[( R )/( S )-L] 4 ]·Cl 5 ·2H 2 O·MeOH·EtOH (Ln = Gd, Dy) (0.02 T –1 ) and 4f complexes (≤0.24 T –1 ) . The large absolute value of g max(MCD) for the chiral Dy 2 enantiomers d - 1 and l - 1 indicates a very strong magneto-optical Faraday effect.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…In Figure b, we observed that the 4 f–5d transition bands of TbCl 3 ⋅6H 2 O and PrCl 3 ⋅ n H 2 O in the MCD spectra exhibit a similar same shape as those in the absorption spectra. According to the general theory, the MCD signals are classified into three terms using the existence or nonexistence of degenerate ground states and excited states as follows , trueIMCDf1A+f2(B+C/kT)…”
Section: Resultsmentioning
confidence: 99%